The Effect of External Debt on Life Expectancy Through Foreign Direct Investment: Evidence from Turkey - Bese, Emrah; Friday, Haven Swint (International Journal of Economics and Financial Issues, 2021)
This is the first study in the single country studies that analyze the relationship between life expectancy, short-term external debt, and long-term external debt for Turkey for the period from 1974 to 2017. This study analyzed the direct effect of long-term debt and short-term debt on life expectancy in Turkey. General tendency in the literature is to analyze the relationship between growth and life expectancy. According to the results in this study, long run relationship is confirmed between the variables. The causal relationship is found from life expectancy to long-term debt and short-term debt but no causal relationship is found from long-term debt and short-term debt to life expectancy. The reason behind this result may result from that Turkey’s increasing life expectancy leads to population increase and the increase in population leads to the increase in the construction of new buildings. For the last 20 years, Turkey started to renew its construction infrastructure and at the same time establishing new buildings for its increasing population. Resulting from that, Turkey needed funding to fund its investments, and it currently is, and there has been a gap between investments and savings in Turkey. Turkey may have used external debt to fund the gap between investments and savings. This article recommends further analysis for the direct relationship between external debt and life expectancy for developing countries. Keywords: Life expectancy; ARDL model; foreign direct investment; long-term external debt; Turkey; short-term external debt JEL Classifications: I18, F10, F40, F20 DOI: https://doi.org/10.32479/ijefi.10958